2019
DOI: 10.1097/gox.0000000000002510
|View full text |Cite
|
Sign up to set email alerts
|

Combination of CAD/CAM and Augmented Reality in Free Fibula Bone Harvest

Abstract: Summary: The CAD/CAM technology for mandibular reconstruction has improved the results in terms of outcomes in restoring mandibular complex defects. Augmented reality (AR) represents an evolution of the navigation-assisted surgery. This technology merges the images of the virtual planning with the anatomy of the patient, representing in this way an enhanced scene for the surgeon’s eye. AR can also display in a single scene additional information for the surgeon. Despite of classical navigation, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 10 publications
0
36
0
Order By: Relevance
“…The VOSTARS device can have prospective use also in tumor and head and neck reconstructive surgery, e.g., in providing anatomical visualization and in supporting mandibular complex reconstruction. Some previous studies reported experiences of AR-assisted navigation used in combination with CAD/CAM technology to guide the positioning of the fibular osteotomy cutting guide [7], as well as to facilitate anatomical visualization during free flap harvesting [42], but in both cases, the AR guidance was performed using hand-held mobile devices (smartphone or tablet). VOSTARS can represent an improved AR-assisted navigation system that allows the surgeon to view directly in front of his eyes the virtual content superimposed on the patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The VOSTARS device can have prospective use also in tumor and head and neck reconstructive surgery, e.g., in providing anatomical visualization and in supporting mandibular complex reconstruction. Some previous studies reported experiences of AR-assisted navigation used in combination with CAD/CAM technology to guide the positioning of the fibular osteotomy cutting guide [7], as well as to facilitate anatomical visualization during free flap harvesting [42], but in both cases, the AR guidance was performed using hand-held mobile devices (smartphone or tablet). VOSTARS can represent an improved AR-assisted navigation system that allows the surgeon to view directly in front of his eyes the virtual content superimposed on the patient.…”
Section: Discussionmentioning
confidence: 99%
“…In the last two decades, new tools based on three-dimensional (3D) imaging and advanced digital technologies have become available to surgeons during pre-, intra-and postoperative phases of an intervention in the cranio-maxillofacial field [4][5][6][7][8], as well as in other surgical specialties, such as neurology, urology, vascular surgery, orthopedics [9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…11,15 An additional step towards the precise medicine and imaging-guided surgery is the adoption of augmented reality (AR) in different surgical interventions. [16][17][18][19][20][21][22] During PN, the AR technology can facilitate a rapid and accurate anatomic identification of the renal vasculature.…”
Section: Clinical Practice Pointsmentioning
confidence: 99%
“…New computer-assisted technologies assist head and neck surgeons in clinical practice [ 10 , 11 ], as does augmented reality (AR). We recently used AR to facilitate anatomical visualisation during free flap harvesting [ 12 ]. Augmented reality merges virtual and actual objects, allowing direct observation of patient anatomy and the surgical field.…”
Section: Introductionmentioning
confidence: 99%
“…This enhances the surgeon’s view of the physical environment without any need for invasive preoperative placement of fixed fiducial markers. Augmented reality offers real-time image registration without the need for markers [ 12 ].…”
Section: Introductionmentioning
confidence: 99%